Seawater carbonate chemistry and sperm and adult biomarkers in the mussel Mytilus galloprovincialis in a multi-stressor context - Alessia Cuccaro; Anthony Moreira; Lucia De Marchi; Valentina Meucci; Amadeu M V M Soares; Carlo Pretti; Rosa Freitas (PANGAEA, 2025)
This study investigated the combined impacts of UV-filters 4-methylbenzylidene camphor (4-MBC) and benzophenone-3 (BP-3), at ecologically relevant concentrations (1 and 10 μg/L), under two target pH levels (8.2 and 7.7, reflecting a ?pH of 0 and -0.3 relative to the average pH at the sampling site), on the biochemical performance and male reproductive health of the mussel Mytilus galloprovincialis. This dataset is included in the OA-ICC data compilation maintained in the framework of the IAEA Ocean Acidification International Coordination Centre (see https://oa-icc.ipsl.fr). Original data were provided by the author of the related paper (see Related to) to the OA-ICC data curator. In order to allow full comparability with other ocean acidification data sets, the R package seacarb (Gattuso et al, 2024) was used to compute a complete and consistent set of carbonate system variables, as described by Nisumaa et al. (2010). In this dataset the original values were archived in addition with the recalculated parameters (see related PI). The date of carbonate chemistry calculation by seacarb is 2025-02-17.